The repeatability and heritability of traits derived from accelerometer sensors associated with grazing and rumination time in an extensive sheep farming system - Almasi, Fazel; Stear, Michael J.; Khansefid, Majid; Nguyen, Hien; Desai, Aniruddha; Pryce, Jennie E. (Frontiers in Animal Science, 2023)
The automated collection of phenotypic measurements in livestock is of interest to both researchers and farmers. The real-time, low-cost and accurate phenotyping can enhance precision livestock management and could lead to optimised pasture utilization and breeding for efficient animals. Wearable sensors provide the tools for researchers to develop novel phenotypes across all production systems, which is especially valuable for grazing conditions. The objectives of this study were to estimate the repeatability and heritability of traits related to grazing and rumination activities, as well as their correlations with other traits. This study was conducted on a commercial Merino farm in the west of Victoria, Australia from 4 to 29 th of May 2020. There were 160 ActiGraph sensors embedded in halters attached to the left side of the muzzle of Merino sheep (M=74, F=86) aged 10-11months whilst grazing on pasture. Support Vector Machine (SVM) algorithms classified the sensor output into grazing, rumination, walking, idle, and other activities. The classified activities were summarised into daily grazing time (GT), number of grazing events (NGE), grazing length (GL), rumination time (RT), number of rumination events (NRE), rumination length (RL), walking time (WT), and idle time (IT). The data were analysed using univariate and bivariate models in ASReml-SA to estimate repeatability, heritability, and phenotypic correlations between traits. The heritability of GT was estimated to be 0.44±0.23, whereas the other traits had heritability estimates close to zero. The estimated repeatability for all traits was moderate to high with the highest estimate for GT (0.70±0.03) and the lowest for RT (0.44±0.03). The intra-class correlation or repeatability with a one day interval (i.e., two consecutive days) was high for all traits, and steadily reduced when the interval between measurements extended beyond one week. The estimated repeatability for the grazing traits showed that wearable sensors and OFFICIAL OFFICIAL SVM methods were reliable methods to record sheep activities on pasture, with a potential application to rank animals for selective breeding.